Imnul acatist - scriere literară și teologică - Lucia Toader (Revista de Istorie și Teorie Literară)
Lucia Toader analyzes The Akathistos, probably dating from 626 A.D., an important religious ceremony, defining the Christian religion and tradition. The analysis is as detailed as possible, since each stanza is translated and described, together with all the figures of speech present in the poem.